Quantifying cost of disease in livestock: a new metric for the Global Burden of Animal Diseases - Gilbert, W.; Marsh, T.L.; Chaters, G.; Jemberu, Wudu T.; Bruce, M.; Steeneveld, W.; Afonso, J.S.; Huntington, B.; Rushton, J. (Elsevier, 2024)
Background: Increasing awareness of the environmental and public health impacts of expanding and intensifying animal-based food and farming systems creates discord, with the reliance of much of the world's population on animals for livelihoods and essential nutrition. Increasing the efficiency of food production through improved animal health has been identified as a step towards minimising these negative effects without compromising global food security. The Global Burden of Animal Diseases (GBADs) programme aims to provide data and analytical methods to support positive change in animal health across all livestock and aquaculture animal populations.